2018
DOI: 10.1177/0022034518798810
|View full text |Cite
|
Sign up to set email alerts
|

The Mutational Profile of Unicystic Ameloblastoma

Abstract: BRAF V600E is the most common mutation in conventional ameloblastoma (AM) of the mandible. In contrast, maxillary AMs appear to harbor more frequently RAS, FGFR2, or SMO mutations. Unicystic ameloblastoma (UAM) is considered a less aggressive variant of ameloblastoma, amenable to more conservative treatment, and classified as a distinct entity. The aim of this study was to characterize the mutation profile of UAM ( n = 39) and to compare it to conventional AM ( n = 39). The associations between mutation status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
80
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 25 publications
6
80
1
7
Order By: Relevance
“…Despite the pathological similarities between CAA and AM, the data show a notable difference in the frequency of the HRAS p.Q61R mutation. Contrasting with our findings, only 20% of AM harbour RAS mutations, with HRAS p.Q61R occurring with a frequency of 6% or less (Figure ) . Similarly, while two‐thirds or more of AM harbour a BRAF p.V600E mutation, the results of this and previous studies show that homologous mutations are either not present in CAA or occur at low frequency.…”
Section: Clinical Information and Hras Mutation Status Of Dogs Includcontrasting
confidence: 99%
See 4 more Smart Citations
“…Despite the pathological similarities between CAA and AM, the data show a notable difference in the frequency of the HRAS p.Q61R mutation. Contrasting with our findings, only 20% of AM harbour RAS mutations, with HRAS p.Q61R occurring with a frequency of 6% or less (Figure ) . Similarly, while two‐thirds or more of AM harbour a BRAF p.V600E mutation, the results of this and previous studies show that homologous mutations are either not present in CAA or occur at low frequency.…”
Section: Clinical Information and Hras Mutation Status Of Dogs Includcontrasting
confidence: 99%
“…Recent discoveries have shown that the majority of human ameloblastomas (AM) are driven by mutually‐exclusive BRAF , HRAS , NRAS , KRAS or FGFR2 mutations that activate the MAPK pathway regulating cell survival . Co‐occurring SMO mutations that alter the Hedgehog signalling pathway to regulate cell fate have also been detected, especially in maxillary tumours .…”
Section: Clinical Information and Hras Mutation Status Of Dogs Includmentioning
confidence: 99%
See 3 more Smart Citations